Analysis of Financial Performance Assessment Based on The Du Pont System on Pharmaceutical Industry Companies - Isna Ayustin; Fany Renoisty; Nardi Sunardi (Indonesian Development of Economics and Administration Journal, 2023)
The study aims to analyze the financial performance of the pharmaceutical industry companies listed on the Indonesian Stock Exchange using the Du Pont System approach with Time Series Approach (TSA) and Cross-Sectional Approaching (CSA) through the return on investment (ROI) and return on equity (ROE) ratio during the period 2018-2022. The results showed that the company. Darya Varia Laboratory Tbk. average 0.55% lower than the industry average that is 0.69% said to perform Less Good, PT. Indofarma Tbk. with an average value of 1.23% greater than the industrial average is said to perform well, PT. Kalbe Farma Tbk. average 0.35% lower than the industry average that is 0.69% said to perform Less Good, PT. Merck Tbk. with an average value of 0.78% greater than the industry average is said to perform well, PT. Phapros Tbk. average 0.64% lower than the industry average is 0.69% said to perform Less Good, PT. Pyridam Farma Tbk. with an average value of 0.79% greater than the industrial average is said to perform well, PT. Soho Global Health Tbk. with an average value of 0.78% greater than the industry average is said to perform well, PT. Jamu and Pharmaceutical Industry Side Appears Tbk. average 0.58% lower than the industry average which is 0.69% said to perform Less Good, PT. The pace of Pacific Scan Tbk. average 0.59% lower than the industry average that is 0.69% said to perform Less Good, using the Return On Investment (ROI) and Return on Equity (ROE) analysis with Time Series Approach (TSA) in the period 2018 - 2022 experienced a decline and fluctuation.